Die Koranhermeneutik von Günter Lüling - Tamer, Georges (De Gruyter, 2018)
The present volume offers the first scholarly discussion of Günter Lüling's (1928-2014) work. Lüling's views, long passages of the Qur'ān are originally mere reworking of pre-Islamic Christian hymns have not received the scholarly attention they deserve, since they were published at the beginning of the 70s of the previous century. Lüling attempted to reconstruct an
10.1515/9783110599176
Keywords: Konferenzschrift; Jesus Christus; Lüling; Günter; Hermeneutik; Textgeschichte; Urchristentum